Javanese Family Resilience in Taking Care of Mental Disorder Clients After Pasung - Sulaihah, Sitti; Yusuf, Ah; Nihayati, Hanik Endang (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to find out about Javanese family resilience among those who cared for mental disorder clients after pasung. The study was focused to know how the family adjusts themselves with an inconvenient situation in taking care of mental disorder clients after pasung according to the perspective of the Javanese family. The research used a qualitative design with an interpretive phenomenology approach. The participants were eight family members who cared for mental disorder clients after pasung. The samples were obtained by purposive sampling technique. The data were collected by interview and using field notes, then analyzed by Collaizi technique. This research produced two themes, positive aspects of family resilience and Javanese culture value. The beliefs, compliance values, communication patterns, norms, and the rule of community leaders were able to provide support for achieving family resilience as the positive aspects of family resilience in taking care of mental disorder clients. The willing, accepting, and patient were able to interpret the events that must be confronted so that they were able to carry out coping strategies that were right for themselves as Javanese culture values. This research explained how positive aspects of the two themes above must be managed by the family to survive, rise, and become better in caring for mental disorder clients after pasung. Further research may focus on family role interventions consisting of family, patient, and environmental factors in taking care of mental disorder clients through family resilience.